2008
DOI: 10.1111/j.1471-6402.2007.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional Political Consciousness: Appreciation for Intragroup Differences and Solidarity in Diverse Groups

Abstract: This article introduces an intersectional approach to political consciousness and presents data to demonstrate its importance for predicting solidarity in diverse social change organizations. Women activists (N = 174) completed measures of political consciousness, diversity, and solidarity. As expected, women differed in the degree to which their political consciousness reflected intersectionality (sensitivity to intragroup differences arising from intersections of social identities, such as ethnicity with gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
146
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(151 citation statements)
references
References 30 publications
5
146
0
Order By: Relevance
“…In a previous correlational study of intersectional and singular consciousness, it was found that group solidarity was negatively associated with group diversity, but only when political consciousness was strongly singular and not when it was strongly intersectional (Greenwood 2008). The present research builds on this previous study by directly manipulating intersectional and singular consciousness to determine their effects on appraisals of intra-group differences.…”
Section: Implications For Research On Political Consciousness Solidamentioning
confidence: 69%
See 3 more Smart Citations
“…In a previous correlational study of intersectional and singular consciousness, it was found that group solidarity was negatively associated with group diversity, but only when political consciousness was strongly singular and not when it was strongly intersectional (Greenwood 2008). The present research builds on this previous study by directly manipulating intersectional and singular consciousness to determine their effects on appraisals of intra-group differences.…”
Section: Implications For Research On Political Consciousness Solidamentioning
confidence: 69%
“…A new approach does account for the role of high status group membership in political consciousness (Greenwood 2008). This perspective builds on the theory of intersectionality (Collins 2000;Crenshaw 1994;Dill 1983).…”
Section: Political Consciousnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar questions have been addressed by Ronni Michelle Greenwood (2008), who asked how feminists could unite themselves when race relations structure activist groups. Her results showed that solidarity in an ethnically heterogeneous group is made possible by the development of an intersectional political consciousness.…”
Section: Feminism Racism and Intersectional Political Consciousnessmentioning
confidence: 93%